PERAN SUPERVISI PENGAWAS SEKOLAH MEMODERASI PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU (STUDI PADA GURU SEKOLAH DASAR SE KECAMATAN LIMPUNG) - Suwandi, Prapto (Students Journal of Economic and Management, 2012)
This.Research has goal to analyse the influence work diclipine, work motivation, and supervision with PKG Teacherâs and supervision to moderate the influence work discipline and work motivation for performance teacherâs in elementary school wich public servant setatuet in UPTD Limpung subdistrict (Dinas Pendidikan Pemuda dan Olahraga) Kecamatan Limpung. This research has taken population about 122 class teacherin the kecamatan Limpung wich is public servant statue. Thatâs why this research is taken from all teacher in the elementary school in UPTD Limpung area as a model. The measurement questionare answer use five scale alternation.The result of hypotesise has got that (1) working discipline is negative influence for teacher performance, (2)working motivation give a positive influence for teacher performance, (3) supervision is a good negative influence for teacher performance , (4)supervision interact and working discipline is positive effect for teacher performance. (5)supervision interact and motivation give negative effect for teacher Â performance Key Word : working discipline, working motivation, supervision and teacher performance